2022
DOI: 10.1186/s12941-022-00513-7
|View full text |Cite
|
Sign up to set email alerts
|

Antibiofilm and staphyloxanthin inhibitory potential of terbinafine against Staphylococcus aureus: in vitro and in vivo studies

Abstract: Background Antimicrobial resistance is growing substantially, which necessitates the search for novel therapeutic options. Terbinafine, an allylamine antifungal agent that exhibits a broad spectrum of activity and is used in the treatment of dermatophytosis, could be a possible option to disarm S. aureus virulence. Methods Terbinafine inhibitory effect on staphyloxanthin was characterized by quantitative measurement of staphyloxanthin intermediates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 75 publications
0
7
0
Order By: Relevance
“…In particular, S. aureus has a variety of defense mechanisms which are upregulated following oxidative burst, such as antioxidant enzymes and small molecules . We evaluated VanB2 against a panel of S.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, S. aureus has a variety of defense mechanisms which are upregulated following oxidative burst, such as antioxidant enzymes and small molecules . We evaluated VanB2 against a panel of S.…”
Section: Resultsmentioning
confidence: 99%
“… 45 In particular, S. aureus has a variety of defense mechanisms which are upregulated following oxidative burst, such as antioxidant enzymes and small molecules. 46 We evaluated VanB2 against a panel of S. aureus strains (including methicillin resistant strain MRSA USA300), which exhibited a range of staphyloxanthin pigmentation. Staphyloxanthin is a membrane-bound antioxidant carotenoid responsible for the yellow-orange appearance of many S. aureus strains.…”
Section: Resultsmentioning
confidence: 99%
“…Both bacterial pallet and staphyloxanthin were subjected to FTIR analysis with a spectral scan (4000-400 cm -1 ) using FTIR spectrometer (NICOLET, USA) [28].…”
Section: Fourier-transform Infrared Spectroscopy (Ftir) Analysismentioning
confidence: 99%
“…Previous researches indicated that terbinafine can inhibit Penicillium spp., Trichoderma spp., Acremonium spp., and Staphylococcus spp. [ 12 , 13 ] Therefore, based on the safety and broad-spectrum antifungal properties of terbinafine, it may have potential to be developed as an agricultural fungicide.
Fig.
…”
Section: Introductionmentioning
confidence: 99%